A Socio-Technical Perspective on Urban Analytics: The Case of City-Scale Digital Twins. Issue 1 (3rd April 2021) - Nochta, T.; Wan, L.; Schooling, J. M.; Parlikad, A. K.
ABSTRACT: This paper demonstrates that a shift from a purely technical to a more socio-technical perspective has significant implications for the conceptualization, design, and implementation of smart city technologies. Such implications are discussed and illustrated through the case of an emerging urban analytics tool, the City-scale Digital Twin. Based on interdisciplinary insights and a participatory knowledge co-production and tool co-development process, including both researchers and prospective users, we conclude that in order to move beyond a mere "hype technology, " City-Scale Digital Twins must reflect the specifics of the urban and socio-political context.